Questioning generational labels and their usefulness for church policy (A response to Leslie van Rooi) - De Roest, H (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
First, you quote Hestorff, Kruger and others in order to find ‘defining characteristics’ of Generation Y. You state that Generation Y members have a common philosophy of life, are very busy and at times, stressed out and can often feel lonely, the two last points also being confirmed by the Stellenbosch University inquiry. Often they participate in and develop their identity in a particular peer cluster. It is a generation that is highly ambitious and wants to be successful. They are critical with regard to absolutism. What counts is being genuine, original and authentic. Generation Y members are socially concerned and internet savvy. Despite the diversity, which is a feature of this generation too, the commonality is striking: it allows you, Leslie, to speak of an ‘apparent gap’ with former generations. Second, you assert that Generation Y members are ‘keenly interested in finding a safe place to belong’. The experience with divorces among the previous, baby boomer and X generations may have had, as you suggest, a formative effect upon the core values of the members of the Y generation. You quote Reggie Nel who found that young people highly value their home as a place of care, love and safety. You add that if the family structure does not function or is torn apart young people will have serious difficulties in developing their identity. Third, for the Stellenbosch students, being representative of generation Y, the church and spirituality play an important role. You question the URCSA focus on ethical and doctrinal education and specifically, you raise criticism as to whether this education responds to the needs of the Generation Y-members. Implicitly you seem to suggest that the church can and should play a more formative role. I think this implicit proposal deserves to become more explicit and developed more fully.